Effect of grain size on fatigue cracking at twin boundaries in a CoCrFeMnNi high-entropy alloy - Wang, A.G.; An, X.H.; Gu, J.; Wang, X.G.; Li, L.L.; Li, W.L.; Song, M.; Duan, Q.Q.; Zhang, Z.F.; Liao, X.Z. (Journal of materials science & technology, 2020)
The fatigue cracking behavior at twin boundaries (TBs) in a CoCrFeMnNi high-entropy alloy with three different grain sizes was systematically investigated under low-cycle fatigue. Irrespective of grain size, the change from slip band cracking to TB cracking occurred with increasing the difference in the Schmid factors (DSF) between matrix and twin. However, the required critical DSF for the transition of the dominant cracking mode decreases with decreasing grain size due to the reduced slip band spacing that increases the impingement sites on the TBs and facilitates the coalescence of defects and voids to initiate TB cracks.